ROJIRO Spiritual Education: Guidance Program Creating Peace for Elderly Santri at Raden Rahmat Pesantren - Imas Kania Rahman; Salasiah Binti Hanin Hamjah; Fahrurrozi Fahrurrozi (Jurnal al-Thullab, 2023)
Psychological well-being is everyone's hope, including the elderly. Elderly complaints of physical illness from the geriatric syndrome, anxiety in the face of death, sadness left by a spouse, and feeling lonely because they are far from their children and grandchildren are problems that hinder their psychological well-being. The Raden Rahmat Pondok Pesantren Educational Institution in Semarang is in great demand as a place of study to achieve the psychological well-being of the elderly. The research aims to describe the ROJIRO Raden Rahmat Pondok Pesantren concept and program analysis from the perspective of Permendikbud No 111 of 2014. The research method is descriptive-analytic qualitative. Document data sources, interviews, and observations. The results of the study, ROJIRO is that elderly education aims to build three domains: if rogo, if jiwo, and if roso (ROJIRO). First, rogo (exercise or physical) to meet cognitive aspects (prevention of senility) and health aspects of motor function. Second, jiwo (soul development) fulfills the moral-spiritual and social-emotional aspects. Third, roso (taste processing) meets the artistic, aesthetic, and communication aspects. The ROJIRO concept meets the criteria to be developed into an elderly boarding school guidance and counseling program referring to the standard program structure of Permendikbud No 111 of 2014 consisting of rationale, vision-mission, description of needs, objectives, program components, service areas, operational plans, theme development, evaluation, and budget costs. This structured systematic program can be evaluated periodically and developed continuously. Kesejahteraan psikologis merupakan harapan semua orang, termasuk lanjut usia. Keluhan lansia berupa penyakit fisik akibat sindrom geriatri, kecemasan menghadapi kematian, kesedihan ditinggal pasangan, dan perasaan kesepian karena jauh dari anak cucu merupakan masalah yang menghambat kesejahteraan psikologis mereka. Pondok Pesantren Raden Rahmat Semarang sangat diminati sebagai tempat belajar untuk mencapai kesejahteraan psikologis lansia. Penelitian ini bertujuan untuk mendeskripsikan konsep dan analisis program Pondok Pesantren ROJIRO Raden Rahmat dari perspektif Permendikbud No 111 Tahun 2014. Metode penelitian yang digunakan adalah kualitatif deskriptif-analitik. Hasil penelitian, ROJIRO adalah pendidikan islami untuk lansia bertujuan membangun tiga ranah: olah rogo, olah jiwo, dan olah roso (ROJIRO). Pertama, rogo (olah raga) untuk memenuhi aspek kognitif (pencegahan kepikunan) dan aspek kesehatan fungsi motorik. Kedua, jiwo (olah jiwa) memenuhi aspek moral-spiritual dan sosial-emosional. Ketiga, roso (olah rasa) memenuhi aspek artistik, estetika, dan komunikasi. Konsep ROJIRO memenuhi kriteria untuk dikembangkan menjadi program bimbingan dan konseling pesantren lansia yang mengacu pada standar struktur program Permendikbud No 111 Tahun 2014 yang terdiri dari rasional, visi-misi, analisis kebutuhan, tujuan, komponen program, struktur layanan, rencana operasional, pengembangan tema, evaluasi, dan anggaran biaya. Program ROJIRO yang dirumuskan secara terstruktur dan sistematis dapat dievaluasi secara periodik dan dikembangkan secara berkesinambungan.